Transmission and reflection of a surface wave at a corner of two planes on an isotropic body - PAJEWSKI, W.; SZALEWSKI, M. (Archives of Acoustics, 1983)
This paper reports on an experimental investigation of the diffraction of a Rayleigh wave at a corner of an isotropic solid bounded by two planes forming a dihedral angle with respect to each other.Application of piezoelectric transducers and their appropriate setting on samples permitted the determination of the coefficient of reflection and transmission of Rayleigh waves at a corner and the directional characteristics of transverse waves, with polarisation in a plane perpendicular to the surface of R propagation, radiated at that time by the corner. The results were compared with the results of papers published in the world literature.